Murine Model Imitating Chronic Wound Infections for Evaluation of Antimicrobial Photodynamic Therapy Efficacy - Fila, Grzegorz; Kasimova, Kamola; Arenas, Yaxal; Nakonieczna, Joanna; Grinholc, Mariusz; Bielawski, Krzysztof P.; Lilge, Lothar (Frontiers in Microbiology, 2016)
It is generally acknowledged that the age of antibiotics could come to an end, due to their widespread and inappropriate use. Particularly for chronic wounds alternatives are being thought. Antimicrobial Photodynamic Therapy is a potential candidate, and while approved for some indications, such as periodontitis, chronic sinusitis and other niche indications, its use in chronic wounds is not established. To further facilitate the development of Antimicrobial Photodynamic Therapy in chronic wounds we present an easy to use animal model exhibiting the key hallmarks of chronic wounds, based on full-thickness skin wounds paired with an optically transparent cover. The moisture-retaining wound exhibited rapid expansion of pathogen colonies up to 8 days while not jeopardizing the host survival. Use of two bioluminescent pathogens; methicillin resistant Staphylococcus aureus and Pseudomonas aeruginosa permits real time monitoring of the pathogens. The murine model was employed to evaluate the performance of four different photosensitizers as mediators in Photodynamic Therapy. While all four photosensitizers, Rose Bengal, porphyrin TMPyP, New Methylene Blue and TLD1411 demonstrated good to excellent antimicrobial efficacy in planktonic solutions at 1 to 50 µM concentrations, whereas in in vivo the growth delay was limited with 24-48 hr delay in pathogen expansion for methicillin resistant Staphylococcus aureus, and we noticed longer growth suppression of Pseudomonas aeruginosa with TLD1411 mediated Photodynamic Therapy. The murine model will enable developing new strategies for enhancement of Antimicrobial Photodynamic Therapy for chronic wound infections.